PENGEMBANGAN MEDIA INTERAKTIF BERBASIS MICROSOFT POWERPOINT KELAS IV SEKOLAH DASAR NEGERI 29 PONTIANAK KOTA - Albinus Febrianus; Kartono Kartono; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to produce a product in the form of a validated powerpoint-based learning media. The research method used is research anddevelopment (R&D) by adapting the Borg and Gall design developmentmodel. The data sources of this research are the results of observations,interviews, expert validation, student responses, and documentationduring the use of powerpoint-based learning media. Data collectiontechniques in this study were observation, interviews and questionnaires.The results showed that the powerpoint-based learning media developmentprocess had gone through 7 research steps, namely potential andproblems, data collection, product design, product validation, revision,trial, and final product revision. The feasibility level of the developedlearning media is very good in terms of design and material aspects withan average value of 3.76 and 3.77, and the results of product trials arevery good with an average value of 3.58.Keywords: Development, Microsoft Powerpoint-based Learning Media